Recent trends of blended learning and flipped classroom in Malaysia - Tan, Choy Soon (AWEJ, 2022)
The classroom is where the student and teacher interact, while traditional education uses a Face to-Face classroom. The unprecedented COVID-19 forced education to shift into an online classroom. Still, numerous researches demonstrate that the pedagogical quality in online classrooms is thus compromised as the educators tend to convert existing face-to-face curriculum that less prioritize intellectual interaction into online ways. Blended learning is not a new yet effective teaching pedagogy, which seems suitable to overcome the challenges as mentioned above as it is a combination of traditional and online modes. Thus, this article summarizes the current trend of blended learning implementation in the Malaysian setting into valuable insight for the practitioner to redesign their pedagogy to meet new norms. This paper assessed and analyzed a total of 22 recent publications that extracted from the Web of Science Database based on three themes that are participant, instrument, and disciplinary. All researches address higher education context, mainly the students' perspectives and neglecting other stakeholders' perspectives. Blended learning is proven practical in multidisciplinary but independent curriculum, and pedagogy redevelopment is mandated. The quantitative methodology is preferable by the researcher in the identification of critical governing factors. Overall, the context of blended learning development in Malaysia remains progressively developing by time. In conclusion, the practice of blended learning implementation is getting diffused in Malaysia due to its flexibility and versatility. However, such effective pedagogy lay on collaborative efforts between various stakeholders, including educators, students, institutional management, policymakers, and parent.